Examples of XRF and PIXE imaging with few microns resolution using SLcam® a color X‐ray camera1. (19th February 2015) - Nowak, S. H.; Bjeoumikhov, A.; von Borany, J.; Buchriegler, J.; Munnik, F.; Petric, M.; Renno, A. D.; Radtke, M.; Reinholz, U.; Scharf, O.; Strüder, L.; Wedell, R.; et al.
<x xml:space="preserve">Abstract</x> We present results of recent development of the color X‐ray camera, type SLcam®, allowing detection of X‐ray images with few microns resolution. Such spectral resolution is achieved with the use of high‐quality polycapillary optics combined with sub‐pixel resolution. Imaging of Siemens star resolution test chart reveals that the resolution limit of SLcam® can go down to nearly 5μm. Several real sample examples of measurements carried out at the laboratory, synchrotron, and particle‐induced X‐ray emission beamlines are shown. This is the first time SLcam® is used as particle‐induced X‐ray emission detector. Copyright © 2015 John Wiley & Sons, Ltd.